2019
DOI: 10.1097/lbr.0000000000000559
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of the Utility of Computed Tomography Triage of Pleural Biopsy Strategies in Patients With Pleural Diseases

Abstract: Background: This study aimed to prospectively evaluate the efficacy and reliability of a diagnostic workup, triaging pleural biopsy method according to baseline computerized tomography (CT) findings in the diagnosis of pleural diseases.Methods: Patients with pleural pathology were divided into 3 arms according to findings on CT scan images. Arm A: patients with pleural thickening/lesion in addition to pleural effusion. These patients underwent CT scan-guided Abrams' needle pleural biopsy. Arm B: patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…We also found that using PFC plus pleural chemiluminescence immunoassay for carcinoembryonic antigen better results might be achieved (5). Other diagnostic tools, such as 18 F-fluorodeoxyglucose positron-emission tomography-and CT-guided pleural biopsy are expensive or invasive, offering similar outcomes (1,20). Talc pleurodesis and indwelling pleural catheter are the procedures available to treat malignant PE; the latter may result in a reduction of the hospital stay (24).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…We also found that using PFC plus pleural chemiluminescence immunoassay for carcinoembryonic antigen better results might be achieved (5). Other diagnostic tools, such as 18 F-fluorodeoxyglucose positron-emission tomography-and CT-guided pleural biopsy are expensive or invasive, offering similar outcomes (1,20). Talc pleurodesis and indwelling pleural catheter are the procedures available to treat malignant PE; the latter may result in a reduction of the hospital stay (24).…”
Section: Discussionmentioning
confidence: 83%
“…The advantages of dualenergy spectral CT has also been reported, showing that in selected patients, the sensitivity and specificity may reach 100% and 71%, respectively (19). In a group of patients who underwent CT scan-guided Abram's needle pleural biopsy, the sensitivity of this minimally invasive procedure ranged from 90.2% to 95.2%, according to the CT findings (20).…”
Section: Discussionmentioning
confidence: 96%